1993
DOI: 10.1002/1097-0142(19930115)71:2<493::aid-cncr2820710235>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

The syndrome of 5-fluorouracil cardiotoxicity. An elusive cardiopathy

Abstract: Background. A case of reversible cardiogenic shock linked to 5‐fluorouracil (5‐FU) was observed. Recognizing the increasing use of 5‐FU, the authors tried to map this syndrome. Methods. They reviewed 134 additional case reports, retrieved information from literature searches, focused on clinical features, and discussed possible pathophysiologic findings and prevention of this syndrome. Results. Although angina and electrocardiographic changes were common and reproducible (approximately 90% each), coronary arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
105
1
4

Year Published

1993
1993
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(116 citation statements)
references
References 78 publications
5
105
1
4
Order By: Relevance
“…Vascular toxicity is a known side-effect of 5-FU/Leucovorin, most often presenting like coronary vasospasms, but solitary bowel ischaemia has also been described (Fata et al, 1999). The precise mechanisms behind these circulatory changes are unknown (Robben et al, 1993). Overall, in this study the toxicity seen after chemotherapy was not different from the toxicity of previous studies using 5-FU/Leucovorin, and thus appears not to be influenced by the immunotherapy given in our clinical trial.…”
Section: -Fu+asi For Stage III Colon Cancer a Baars Et Alcontrasting
confidence: 55%
“…Vascular toxicity is a known side-effect of 5-FU/Leucovorin, most often presenting like coronary vasospasms, but solitary bowel ischaemia has also been described (Fata et al, 1999). The precise mechanisms behind these circulatory changes are unknown (Robben et al, 1993). Overall, in this study the toxicity seen after chemotherapy was not different from the toxicity of previous studies using 5-FU/Leucovorin, and thus appears not to be influenced by the immunotherapy given in our clinical trial.…”
Section: -Fu+asi For Stage III Colon Cancer a Baars Et Alcontrasting
confidence: 55%
“…This DNA-directed antimetabolite mechanism is therefore a very unlikely cause of 5-FU cardiotoxicity. As the recurrence rate of cardiotoxicity after exposure to 5-FU is thought to be 90% (Robben et al, 1993), cardiotoxic side-effects after a total of seven exposures to raltitrexed would have been expected, assuming that the direct cytotoxic effect on DNA synthesis is responsible for cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Trombogenicity of intravenous infusion of 5-FU has been suggested as a causative factor (1). Previous studies have shown that rheological changes are involved in a variety of cardiovascular diseases (20)(21).…”
Section: Discussionmentioning
confidence: 99%